2017
DOI: 10.3892/or.2017.5927
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NOB1 by microRNA-330-5p overexpression represses cell growth of non-small cell lung cancer

Abstract: MicroRNAs (miRNAs) play critical roles in the development and progression of various cancers, including non-small-cell lung cancer (NSCLC). Studies have suggested that miR-330-5p is involved in the progression of several cancers. However, the role of miR-330-5p in NSCLC remains unclear. We investigated the effect on and mechanism of miR-330-5p in the progression of NSCLC. We found that miR-330-5p was significantly downregulated in NSCLC tissues and cell lines as detected by real-time quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…16 MiRNA (miR)-330-5p is downregulated in multiple malignant tumors, such as glioblastoma, colorectal cancer, prostate cancer, [17][18][19] and NSCLC as well. 20 The 3-phosphoinositide-dependent protein kinase-1 (PDK1), one crucial node of the PI3K pathway, can physically phosphorylate AKT. 21 Moreover, PDK1 is a key oncogene to promote NSCLC cell growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…16 MiRNA (miR)-330-5p is downregulated in multiple malignant tumors, such as glioblastoma, colorectal cancer, prostate cancer, [17][18][19] and NSCLC as well. 20 The 3-phosphoinositide-dependent protein kinase-1 (PDK1), one crucial node of the PI3K pathway, can physically phosphorylate AKT. 21 Moreover, PDK1 is a key oncogene to promote NSCLC cell growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The mutant sequence of miR-330 is miR-330-5p, and several studies reported that miR-330-5p unction as oncogenes or tumor suppressor genes in tumor progression such as breast cancer, lung cancer, prostate cancer, PC, etc. [28][29][30][31] MiRNAs can regulate tumorogenesis by regulating their target mRNAs, and miR-330-5p directly bound to RASSF1 3′-UTR. Recent evidence indicated that RASSF1 is involved in various biological processes such as apoptotic signaling, microtubule stabilization, and mitotic progression, etc.…”
Section: Discussionmentioning
confidence: 99%
“…NOB1 could cleave RNA substrate that contains the D site of pro-ribosomal RNA, thereby regulating protease functions and RNA metabolism [16]. NOB1 acted as an oncogene and was upregulated in a variety of cancers that include cervical cancer, gastric cancer, epithelial ovarian cancer, and non-small cell lung cancer [18][19][20][21]. Silencing of NOB1 could inhibit cell growth and metastasis of laryngeal cancer and colorectal cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The RNA substrate containing the D site of pro-ribosomal RNA is efficiently cleaved by NOB1 in a manganese-dependent manner, thereby regulating protease function and RNA metabolism [17]. NOB1 was upregulated and acted as an oncogene in a variety of cancers including cervical cancer, gastric cancer, epithelial ovarian cancer, and non-small cell lung cancer [18][19][20][21]. In laryngeal cancer, Gao et al have discovered that silencing of NOB1 could inhibit cell growth and metastasis [22].…”
Section: Introductionmentioning
confidence: 99%